KB004, a first in class monoclonal antibody targeting the receptor tyrosine kinase EphA3, in patients with advanced hematologic malignancies: Results from a phase 1 study. (November 2016) - Swords, Ronan T.; Greenberg, Peter L.; Wei, Andrew H.; Durrant, Simon; Advani, Anjali S.; Hertzberg, Mark S.; Lewis, Ian D.; Rivera, Gabriel; Gratzinger, Dita; Fan, Alice C.; Felsher, Dean W.; Cortes, Jorge E.; et al.
Highlights: KB004 is a novel anti-ephrin novel monoclonal antibody targeting EphA3. KB004 was safe and relatively well-tolerated in patients with myeloid neoplasms. Manageable infusion reactions were dose limiting. There was clinical activity in patients with fibrotic MDS and myelofibrosis. Abstract: EphA3 is an Ephrin receptor tyrosine kinase that is overexpressed in most hematologic malignancies. We performed a first-in-human multicenter phase I study of the anti-EphA3 monoclonal antibody KB004 in refractory hematologic malignancies in order to determine safety and tolerability, along with the secondary objectives of pharmacokinetics (PK) and pharmacodynamics (PD) assessments, as well as preliminary assessment of efficacy. Patients were enrolled on a dose escalation phase (DEP) initially, followed by a cohort expansion phase (CEP). KB004 was administered by intravenous infusion on days 1, 8, and 15 of each 21-day cycle in escalating doses. A total of 50 patients (AML 39, MDS/MPN 3, MDS 4, DLBCL 1, MF 3) received KB004 in the DEP; an additional 14 patients were treated on the CEP (AML 8, MDS 6). The most common toxicities were transient grade 1 and grade 2 infusion reactions (IRs) in 79% of patients. IRs were dose limiting above 250 mg. Sustained exposure exceeding the predicted effective concentration (1ug/mL) and covering the 7-day interval between doses was achieved above 190 mg. Responses were observed in patients with AML, MF, MDS/MPN and MDS. In this study, KB004 was well tolerated and clinically active when given as a weekly infusion.